Microsoft Office 2010 : a lesson approach - Hinkle, Deborah; Stewart, Kathleen ;Graves, Pat ;Mayhall, Amie ;Juarez, Jon;Carter, John (New York : McGraw Hill Education, 2011)
McGraw-Hill is proud to introduce the Hinkle et al., "Office 2010: A Lesson Approach Series". Utilizing the author team of Deborah Hinkle, Kathleen Stewart, John Carter and Pat Graves from the former "Professional Approach Series for Microsoft Office", this "Office 2010: Lesson Approach" series provides a fresh, clear, modular introduction of Microsoft Office 2010 skills. It's 'Learn by Doing' theme is incorporated in each lesson so students can experience hands-on learning throughout the entire text. Students first focus on the introductory skills that are isolated in each lesson and then complete individual skill exercises that ensure a clear learning path. The application case studies provide even more context to the student so they can better associate lesson goals and themes. This text also correlates with SimNet Online for Office 2010, our online training and assessment program, and also SimGrader, our online project grader component which contains a full project library including projects from this Lesson Approach Series and also projects from our other Microsoft Office 2010 textbook series. Together, SimNet and SimGrader provide the complete solution for today's student learning Microsoft Office 2010.
Unit 1. Basic Skills -- Unit 2. Paragraph Formatting, Tabs, and Advanced Editing -- Unit 3. Page Formatting .
Includes index.
Keywords: MICROSOFT OFFICE